Reduction of concentrations of sodium chloride in food aiming blood pressure homeostasis - Martelli, Anderson (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Arterial hypertension (AH) is a multifactorial clinical condition characterized by high levels of blood pressure. Excessive intake of sodium, mineral often present in food, has been correlated with the HA. This review aims to describe the relationship between excessive consumption of sodium and the development and/or aggravation of hypertension and how their reduction in the diet can control blood pressure levels. The survey was conducted from a literature review of the literature, consulted with scientific articles published by 2013 and further consultation with academic books to complement the information. Studies based on dietary surveys show that the Brazilian population has a high sodium intake which stems primarily of salt and condiments with this ingredient, but also indicate that there is a linear increase of total heavy and sodium coming from processed foods, been described in several studies that excessive sodium intake increases blood pressure enhancing the development of other cardiovascular diseases.